The Concept of Love in 17th and 18th Century Philosophy - Moors, M. (Martin), 1947-; Dijn, Herman de, 1943-; Boros, Gábor (Book collections on Project MUSE., 2007)
""Love is joy with the accompanying idea of an external cause."" Spinoza's definition of love (Ethics Book 3, Prop. LIX) manifests a major paradigm shift achieved by seventeenth century Europe in which the emotions, formerly seen as normative ""forces of nature, "" were embraced by the new science of the mind. We are determined to volition by causes. This shift has often been seen as a transition from a philosophy laden with implicit values and assumptions to a more scientific and value-free way of understanding human action. But is this rational approach really value-free? Today we incline to